Development Model of Sustainable Agrotourism-Based Village Tourism for Improving Community Welfare in Tapanuli Utara Regency, Indonesia - Riady, Iwan; ., Sirojuzilam; Purwoko, Agus; Lubis, Satia Negara; ., Charloq (Journal of Ecohumanism, 2024)
This study examines the impact of village tourism development on sustainable agrotourism and community welfare in Tapanuli Utara Regency, Indonesia. Utilizing a mixed-methods approach that combines household surveys and structural equation modeling (SEM), data were collected from 203 respondents across 22 villages to evaluate the relationships among infrastructure development, local economic benefits, community participation, rural tourism products, sustainable agrotourism, and community welfare. The results indicate that village tourism development significantly and directly enhances both sustainable agrotourism and community welfare, with infrastructure and local economic benefits being the most influential factors. In contrast, community participation and rural tourism products did not show significant individual effects, suggesting that without proper support, training, and resource allocation, these elements may not effectively contribute to sustainable agrotourism. Moreover, sustainable agrotourism was found to significantly mediate the relationship between tourism development and community welfare, highlighting its role as a catalyst for long-term socio-economic improvement. The study underscores the necessity for integrated development strategies that prioritize infrastructure enhancement and local economic engagement while fostering sustainable agricultural practices within tourism. Limitations of the study include its regional focus, which may affect the generalizability of the findings, and the need for further research to explore effective mechanisms for boosting community participation and developing rural tourism products. These insights offer valuable guidance for policymakers and stakeholders aiming to promote sustainable rural tourism and enhance community welfare in similar contexts.